UJI AKTIVITAS ANTIOKSIDAN KOMBINASI EKSTRAK ETANOL DAUN TEH HIJAU (Camellia Sinensis L.) DENGAN EKSTRAK ETANOL KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) MENGGUNAKAN METODE DPPH - Illah, Galuh Sekar Rahma; Rejeki, Endang Sri; Pramukantoro, Ganet Eko (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2024)
Red dragon plant (Hylocereus polyrhizus) and green tea (Camellia Sinensis L.) are plants that have benefits as antioxidants. Antioxidant compounds are able to reduce free radicals so that they become harmless substances. The purpose of this study was to determine the potential antioxidant activity of the combination of green tea leaves and red dragon fruit peels by making three comparisons, namely 1:1, 1:2, 2:1. Extraction was carried out by maceration using 96% ethanol solvent to obtain a thick extract. The extract was subjected to phytochemical screening, then the viscous extract was made into 3 combination variations, namely 1:1, 1:2, and 2:1. In testing the antioxidant activity using the DPPH method spectrophotometrically. The results of data on the percentage of antioxidant activity were tatistically analyzed using SPSS with the one way ANOVA method. The research results show that the combination of green tea leaves and red dragon skin has strong antioxidant activity. The IC50 value at a 1:1 ratio is 13.25 ppm, at a 1:2 ratio is 12.15 ppm, and at a 2:1 ratio is 11.40 ppm. The 2:1 ratio is the strongest combination.